Precision measurement of the longitudinal double-spin asymmetry for dijet production at intermediate pseudorapidity in polarized pp collisions at √s = 200 GeV - Aboona, Bassam; Herrmann, Norbert; Leung, Yue; Söhngen, Yannick; Weidenkaff, Philipp (Physical review, 2025)
The STAR Collaboration reports precise measurements of the longitudinal double-spin asymmetry, 𝐴𝐿⁢𝐿, for dijet production with at least one jet at intermediate pseudorapidity 0.8<𝜂jet<1.8 in polarized proton-proton collisions at a center-of-mass energy of 200 GeV. This study explores partons scattered with a longitudinal momentum fraction (𝑥) from 0.01 to 0.5, which are predominantly characterized by interactions between high-𝑥 valence quarks and low-𝑥 gluons. The results are in good agreement with previous measurements at 200 GeV with improved precision and are found to be consistent with the predictions of global analyses that find the gluon polarization to be positive. In contrast, the negative gluon polarization solution from the JAM Collaboration is found to be strongly disfavored.